Road defect causes by underground infrastructure installation - Syahida Asma , Ab Aziz (2013)
In the era of technology advancement and sophisticated, Malaysia is among of the developing country with the increasing of road users. There are many of new project being launched include with the construction of underground infrastructure. The construction of underground infrastructure is made up of assembly the electrical cable, water supply, sewerage, telecommunication cable and so on. The research of underground infrastructure process has been carried Out at the State of Kelantan. The underground infrastructure maintenance to some extent affects the, road surface with the deterioration of road. The questionnaires have been distributed to the 50 respondents and the data analyzed throughout the relative average index. The method of underground infrastructure installation have been analyzed from the questionnaire is open cut, horizontal direct drilling, micro-tunneling, thrust boring, pipe jacking and pipe ramming. The analysis also determines the type of road defect occurs after the underground infrastructure installation done is crack, depression, and pothole, and raveling, delamination, rutting and bleeding.